Aspergillus nidulans BapH is a RAB11 effector that connects membranes in the Spitzenkörper with basal autophagy. Issue 3 (13th September 2017) - Pinar, Mario; Peñalva, Miguel A.
Summary: Using affinity chromatography we identified the Aspergillus nidulans F‐BAR‐and‐PH domain‐containing protein BapH as a RabE RAB11 effector. BapH localizes to the Spitzenkörper (SPK) in an F‐actin‐ and Sec7‐dependent manner, becoming cytosolic after inactivation of Trs120 in TRAPPII, the oligomeric GEF for RabE RAB11 . Therefore, RabE RAB11 contributes to the recruitment of BapH to secretory vesicles in vivo . BapH has a close homologue, SlmA, which is related to yeast Slm1p/Slm2p, localizes to eisosomes and does not bind RabE RAB11 . bapHΔ, slmAΔ and double bapHΔ slmAΔ mutations do not affect growth, although slmAΔ results in myriocin hypersensitivity. Both the PH and the F‐BAR domain in BapH are necessary to recruit the protein to membranes, whereas its C‐terminal moiety negatively regulates localization to the SPK. Strong overexpression of full‐length BapH or of BapH lacking the C‐terminal moiety impairs growth. The tandemly duplicated PH BapH domain is recruited to the plasma membrane in a manner dependent on critical Lys residues in its 'noncanonical' lipid binding pocket, suggesting that it binds to biological membranes containing PtdIns(4, 5)P2 . Ablation of BapH, or deletion of the PH or BAR domains critical for the SPK localization increases autophagy under nitrogen‐replete conditions. Therefore, BapH localizing to SPK vesicles influences basal levels of autophagy. Abstract : RabE/RAB11 is a key regulator of exocytosis in fungal hyphae. The effectors that this GTPase recruits to play its physiological roles are unknown. Here, we report on one such effector that appears to connect secretory membranes in the Spitzenkörper with autophagy.